Spinal Trauma: a case report - Nasrullah Mustamir (Neurologico Spinale Medico Chirurgico, 2018)
Introduction: The incidences of both car accident and sport accident have been increasing lately in Indonesia. One of the big problems is about the trauma of the spine. Cervical spine trauma is the most dangerous case. Herein we report one case of Odontoid Fracture Type II. Methods: A 24-years-old man had an accident after jumping into a shallow swimming pool. The patient bumped his head into the floor and suffered from tetraparesis. After that, he was getting better step-by-step. Approximately 3 months later, the patient bumped his head again on a branch of a tree and regressed to tetraparesis again. We established odontoid fracture type II diagnosis from plain cervical x-ray. We decided to do a surgery by using pedicle screws at CII, lateral mass at CI, and fusion at CI and CII. Result: After the surgery, the patient’s health improved. Six months after the operation, the patient recovered well. Conclusion: We can do this operation without c-arm, we performed this operation by free-hand and anatomy landmark.